EFEKTIVITAS PELAYANAN KESEJAHTERAAN SOSIAL BERBASIS ONLINE PADA DINAS SOSIAL KABUPATEN SUMBAWA BARAT - ANDY SUWANDY; SUPARMAN SUPARMAN; NAJAMUDIN NAJAMUDIN (Universitas Mahasaraswati K. Mataram, 2023)
This research discusses the Effectiveness of Online-Based Social Welfare Services at the West Sumbawa District Social Office. It focuses on the effectiveness and quality of online-based social welfare services provided by the West Sumbawa District Social Office. This research aims to understand the impact and progress of online-based service implementation in the context of social welfare. This study utilizes a quantitative descriptive approach to gather the necessary data to measure the effectiveness and quality of social welfare services at the West Sumbawa District Social Office. The results of the analysis of the effectiveness of online-based social welfare services show that the implementation significantly improves the effectiveness of social welfare services. Factors such as the implementation of standard operating procedures, timeliness of service completion, cost transparency, quality of facilities and infrastructure, staff behavior, and qualifications all have a positive impact on service performance.